Efecto de combinaciones de abonos orgánicos y minerales sobre la productividad del cultivo de plátano - Mendieta Álvarez, Humberto Adrián (2018)
The objective of the research was to evaluate the effect of combinations of organic and mineral fertilizers on the productivity of the plantain crop. The experiment was carried out from May 2017 to July 2018 at the Manabí Polytechnic School "Manuel Félix López". Fertilization treatments were evaluated: (T1) conventional fertilization (220 N, 110 P2O5, 440 K2O), (T2) 50% chemical fertilization (110 N, 55 P2O5, 220 K2O) + 50% compost (3 t) ha-1), (T3) 25% chemical fertilization (55 N, 27 P2O5, 110 K2O) + 75% compost (4.5 t ha-1), (T4) 100% compost (6 t ha-1) and (T5) 50% chemical fertilization (110 N, 55 P2O5, 220 K2O). The data were subjected to analysis of variance and separation of means with the Tukey test at 5% of error probabilities. The main variable evaluated was yield in t ha-1. The results showed that the highest yield was obtained with conventional fertilization with 30.48 t ha-1 and the proportion of 50% of chemical fertilization + 50% of compost (3 t ha-1) with 27.22 t ha-1 , this in relation to the other treatments that achieved lower yields. Compost as a fertilizer was not an effective source to increase crop yield. However when combined with mineral fertilizers significantly increases the productivity of the crop.